The question of Palestine & the United Nations - United Nations Dept. of Public Information ([New York?] United Nations Dept. of Public Information, 2003)
A primer on the question of Palestine and the role of the United Nations, the book explores the spiral of violence in the Middle East, and "the legal framework under which a comnprehensive, just and lasting peace could be established in the region." Up-to-date as of October 2001
"DPI/2276."
"March 2003."
"Published by the United Nations Dept. of Public Information"--P. 4 of cover
Includes bibliographical references
1
Keywords: United Nations -- Palestine; Arab-Israeli conflict -- 1993-; Palestinian Arabs -- Legal status, laws, etc; Palestine -- International status